Characteristics of Glucose Oxidase Gene (GGOx) from Aspergillus niger IPBCC 08.610 - Popi Asri Kurniatin; Laksmi Ambarsari; Annisa Dhiya Athiyyah Khanza; Inda Setyawati; Djarot Sasongko Hami Seno; Waras Nurcholis (Syarif Hidayatullah State Islamic University, 2020)
Glucose oxidase is used in various industries for the development of enzymatic fuel cell. Based on prior studies, this compound is sourced from the local isolates of Aspergillus niger IPBCC 08.610, although investigations on the encoding gene have not been conducted. The purpose of this research, therefore, is to identify and characterized the gene responsible for encoding glucose oxidase, in the aspect of sequence, length, and restriction patterns. This experiment involved the amplification of genomic DNA using specific primers for gene recognition, which was followed by the restriction technique with EcoRI and PstI endonucleases. Furthermore, the gene is inserted into vector pGEM®T-Easy and transformed into competent E. coli DH5α cells, in an attempt to perform sequencing. The glucose oxidase gene from A. niger IPBCC 08.610 was confirmed to possess a size of 1848 bp, and a GC content of 57.8%, with a possibility of restriction into two fragments of size 908 bp and 980 bp, using the EcoRI restriction.